Green Technology Innovation and Financial Performance: Roles of Executive Green Perception and Carbon Performance - Yan Li; Pankaewta Lakkanawanit; Muttanachai Suttipun; Wilawan Dungtripop; Rizqa Anita (Emerging Science Journal, 2026)
Existing research on the linkage mechanisms among green technology innovation (GTI), executive green perception (EGP), carbon performance (CP), and financial performance (FP), particularly systematic investigations within the context of China’s high‑carbon industries, remains insufficient. To address this gap, this study explored the pathway through which GTI influences FP, as well as the mediating effect of EGP and the moderating effect of CP. Grounded in stakeholder theory and innovation diffusion theory, an integrated analytical framework was developed and tested using panel data from listed companies in China’s coal, energy, and manufacturing sectors spanning 2015 to 2023 (N = 11,302). The analysis employed a two-way fixed effects model. The results revealed that GTI significantly and positively impacts FP (β = 0.199, p < 0.01), with EGP serving a partial mediating role in this relationship. Furthermore, CP positively moderates the connection between GTI and FP (β = 0.096, p < 0.01). The key innovation of this research is its unique simultaneous examination of both mediating and moderating mechanisms within a single model. The approach provides a deeper theoretical explanation and practical managerial insights for utilizing green innovation to enhance financial outcomes in high-carbon transitional settings.